Methodological approaches to the analysis of labor rationing in the organization ("Journal "U". Economy. Management. Finance.", 2024)
This article describes the process of analyzing the state of labor rationing in an enterprise, ways to implement and improve it using various methods. The object of the study is the rationing of labor, the subject of the study is its state in the organization. The study proposes parameters for the analysis of labor rationing. Based on the results of their application, companies will be able to analyze the labor costs of their subordinates, evaluate their effectiveness and potential.
Keywords: standards; labor standards; methodology; analysis; labor process; indicators